Study of the Four Objections on the Viewpoint of Non-effectiveness of Conceptual Appropriations Contradicting Contractual Commitment - Ã™Â‚Ã™Â†Ã™ÂˆÃ˜Â§Ã˜ÂªÃ›ÂŒ, Ã˜Â¬Ã™Â„Ã›ÂŒÃ™Â„; Ã˜Â¹Ã™Â„Ã™ÂˆÃ›ÂŒ Ã™Â‚Ã˜Â²Ã™ÂˆÃ›ÂŒÃ™Â†Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã˜Â¹Ã™Â„Ã›ÂŒ; Ã˜Â¹Ã™Â„Ã›ÂŒÃ˜Â²Ã˜Â§Ã˜Â¯Ã™Â‡, Ã˜Â¹Ã˜Â¨Ã˜Â¯Ã˜Â§Ã™Â„Ã˜Â±Ã˜Â¶Ã˜Â§; Ã˜ÂµÃ™ÂÃ˜Â±Ã›ÂŒ, Ã˜Â§Ã˜Â³Ã™ÂÃ™Â†Ã˜Â¯Ã›ÂŒÃ˜Â§Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
In the cases in which, according to a contract, the person is committed to abandon a conceptual appropriation, some jurists believe, according to the uá¹£Å«lÄ« principle denoting prohibition of corruption, that contradictory appropriations are sound. In contrast to the above viewpoint, many of the jurists and scholars of principles of jurisprudence have in general claimed with reliance on four reasons that situational ordinance of contradictory appropriation with contractual commitment are sound. In this article, all the above-mentioned four reasons are analytically studied and rejected.